KAJIAN NILAI PCN RUNWAY BERDASAR METODE ANALITIK DAN METODE TEORITIK DI BANDARA H. ASAN SAMPIT - Andius Dasa Putra (UNIVERSITAS LAMPUNG, 2010)
Implementation of air traffic safety is shown from good operation and free from activity which against the law. This statement has declared on Government Regulation about Air Traffic Safety in Indonesia. Analysis of Pavement Classification Number (PCN) value is the one of air traffic safety requirement. Due to that statement, this research try to evaluation and analysis about performance of runway based on analytical method and theoritical method using data from HWD (Heavy Weight Deflectometer) test. The result of performance runway will shown on PCN value.HWD tests are routinely conducted at the FAA to evaluate performance of pavemnet. HWD tests are conducted in two phases.In the first phase, HWD geophone sensors record vertical deflections at seven points on thepavement surface. The collected data are used for pavement evaluation and environment related thickness response analysis. In the second phase, the insitu pavement sensors record the pavement response while the HWD geophones record the defections on the pavement surface. These tests are conducted by placing the HWD load plate directly over the in situ deflection and strain sensors. One of the objectives of the HWD tests is to develop relationships between the applied load and measured deflections.The result of this research has shown that PCN value from analytical method is 9/F/A/X/T and theoritical method is 38/F/D/X/T. Code letter A or D on PCN value is describe about class of bearing capacity of subgrade. That difference of code letter bearing capacity due to HWD test directly collecting data of subgrade reaction under the pavement but the other method has taken data of subgrade from sample outside of runway . Increasing of bearing capacity of subgrade cause process of compaction on subgrade under the pavement has perfectly done.